Implementasi Kualitas Pelayanan Islami terhadap Kepuasan Pasien di Rumah Sakit Tersertifikasi Syariah dan Rumah Sakit tidak Tersertifikasi Syariah - Hafida Zahara Hanun; Budiyono Budiyono; Septo Pawelas Arso (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The growth of sharia hospitals in Indonesia reflects the increasing need of Muslim communities for health services aligned with sharia principles. Sharia certification by DSN-MUI in collaboration with MUKISI serves as the standard for Islamic services, yet many Islamic hospitals implement Islamic services without formal certification. Studies comparing Islamic service quality and patient satisfaction between certified and non-certified sharia hospitals remain limited. This study employed an explanatory sequential mixed-methods design with a cross-sectional approach in the quantitative phase. The study was conducted at Islamic Hospital (sharia-certified) and Islamic Hospital (non-sharia certified). A total of 254 Muslim inpatients were selected through purposive sampling, supplemented by nurse and management informants for in-depth interviews. The independent variable was Islamic service quality (tangible, reliability, responsiveness, assurance, empathy) and the dependent variable was patient satisfaction. Data were analyzed using the Mann-Whitney test, simple linear regression and thematic analysis. Islamic service quality at the certified hospital (mean 35.85) was higher than the non-certified hospital (31.67), with a significant difference (p=0.000). Patient satisfaction was also higher at the certified hospital (72.32 vs 65.39; p=0.000). Islamic service quality positively and significantly affected patient satisfaction at both hospitals, with a greater contribution at the certified hospital (R²=86.3%) than the non-certified hospital (R²=74.7%). Qualitative findings revealed that Islamic services at the certified hospital were more structured and consistent. Sharia certification contributes to improving Islamic service quality and patient satisfaction through a more standardized service system.